2004
DOI: 10.1002/rra.805
|View full text |Cite
|
Sign up to set email alerts
|

Density and distribution of potential prey for larval fish in the main channel of a floodplain river: pelagic versus epibenthic meiofauna

Abstract: Fish larvae require high densities of appropriately sized prey items for their survival and recruitment. It has been widely assumed that inundated floodplains are the major source of high densities of prey in floodplain rivers. This study examined the density and distribution of both pelagic and epibenthic meiofauna in a range of potential larval fish nursery habitats within the main channel of an Australian floodplain river. Although sufficient densities of meiofauna were found in the main channel environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 40 publications
3
51
1
Order By: Relevance
“…The second competing hypothesis, the low-flow recruitment model, emphasizes the importance of low discharge periods for spawning and larval recruitment because prey populations are denser at this time (King, 2004a). Dettmers et al (2001) and King (2004a) found that densities of potential invertebrate prey were sufficient primarily in the epibenthic zone of some large Australian and North American rivers to sustain larval fish in the main channel, while littoral and backwater habitats had only slightly greater densities of meiofauna.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The second competing hypothesis, the low-flow recruitment model, emphasizes the importance of low discharge periods for spawning and larval recruitment because prey populations are denser at this time (King, 2004a). Dettmers et al (2001) and King (2004a) found that densities of potential invertebrate prey were sufficient primarily in the epibenthic zone of some large Australian and North American rivers to sustain larval fish in the main channel, while littoral and backwater habitats had only slightly greater densities of meiofauna.…”
Section: Introductionmentioning
confidence: 97%
“…The flood recruitment model (King, 2004a), which was heavily influenced by the flood pulse concept (FPC; Junk et al, 1989), maintains that flooding is beneficial to fish populations because it allows access to food and habitat in the highly productive and structurally complex floodscape (Thorp et al, in press) of large, unregulated rivers. Although flooding increases horizontal connectivity to the floodscape and may also enhance longitudinal connectivity up-or downstream via ephemeral reaches (Dodds et al, 2004), studies have shown that for species relying on littoral resources, the FPC has only held true in areas with long periods of floodscape inundation (Gutreuter et al, 1999;Bartosova and Jurajda, 2001;Penczak et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meiofauna often dominate benthic invertebrate as semblages and play important roles in assemblage and ecosystem processes (Palmer et al 2006), such as providing a food source for larval fishes (King 2004a,b). However, meiofauna are not sampled effectively using traditional sampling methods that focus on the water column (King 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…High availability of food, low water speed, and reduced predation pressure are some of the main characteristics of these areas (ReynalteTataje et al, 2008a). Environments that are most commonly used by freshwater fish larvae as nurseries include bays, channels, marginal lagoons, pools, margins without currents (Scott & Nielsen, 1989;Agostinho et al, 1993;King, 2004;Reynalte-Tataje et al, 2008a), and floodplains (Daga et al, 2009;Gogola et al, 2010). Floodplain environments are of great importance for the initial stages of Neotropical fish development (Paiva, 1982;Gogola et al, 2010).…”
Section: Introductionmentioning
confidence: 99%